What's on your mind? a visual portrayal of the social life of a wallflower - Fabella, Danielle Tamara Basila; Concepcion, Reynaldo L. (Quezon City College of Fine Arts, University of the Philippines Diliman, 2019)
Amidst an increasingly social global environment, the wallflower remains largely left out. A general impression about wallflowers is that they are strange of weird for having mostly no friends or social circles. In 1999, Stephen Chbosky published his novel "The Perks of Being a Wallflower" which was eventually adapted into film in 2012. Chbosky tells the story of a young teen struggling with social interaction and coming to terms with life growing up. Both the novel and the film helped popularize the use of the term "wallflower" to refer to someone who has difficulty socializing with others. They helped direct the wallflower, ironically so, into the social spotlight, as more and more people began associating themselves with this obscure label.

This thesis attempts to visually illustrate the proponent as a wallflower through a series of narratives depicting her social life. The resulting images of the visual juxtaposition of imagery done in paintings and video serve as a metaphor for the proponent's desire for social connection. In doing this, the proponent is showing the separation she experiences between her desires and her reality as a result of being a social wallflower.
Thesis (Bachelor of Fine Arts in Painting)--University of the Philippines Diliman
Bibliography: leaf 18
Keywords: Social isolation; Narrative art; Self in motion pictures; Acrylic painting